The genetic basis of resistance in Arabidopsis thaliana ecotype Kil-0 against Ralstonia solanacearum isolate BCCF 402 from Eucalyptus - Berger, David Kenneth (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.